1975
DOI: 10.2135/cropsci1975.0011183x001500050033x
|View full text |Cite
|
Sign up to set email alerts
|

Results of Breeding for Tolerance to 2,4‐D in Birdsfoot Trefoil1

Abstract: To develop a weed control system for birdsfoot trefoil (Lotus corniculatus L.) utilizing an effective, inexpensive, and relatively safe herbicide, 2,4‐D, a recurrent selection program was undertaken to breed a strain of trefoil tolerant to this herbicide. We believe that this is the first report of the successful use of recurrent selection to develop herbicide tolerance.A series of tests established that five cycles of field selection had been effective in developing a strain substantially more tolerant to 2,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Traditionally, such plant breeding projects have been conducted using conventional techniques such as recurrent selection (10). Devine et al (7) developed a line of birdsfoot trefoil (Lotus corniculatus L.) tolerant to 2,4-D; five cycles of selection resulted in a significant increase in 2,4-D tolerance levels. Faulkner (9) developed a line of perennial ryegrass (Lolium perenne L. # 3 LOLPE) tolerant to paraquat (1,1'dimethyl-4,4T5ipyridinium ion).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, such plant breeding projects have been conducted using conventional techniques such as recurrent selection (10). Devine et al (7) developed a line of birdsfoot trefoil (Lotus corniculatus L.) tolerant to 2,4-D; five cycles of selection resulted in a significant increase in 2,4-D tolerance levels. Faulkner (9) developed a line of perennial ryegrass (Lolium perenne L. # 3 LOLPE) tolerant to paraquat (1,1'dimethyl-4,4T5ipyridinium ion).…”
Section: Introductionmentioning
confidence: 99%
“…However, the clovers often experience significant seedling stage weed competition while being highly sensitive to 2,4‐D. Previous research in birdsfoot trefoil ( Lotus corniculatus L.) (Devine et al, 1975) showed progress through five cycles of recurrent selection for tolerance to 2,4‐D herbicide. Given the above, we initiated a program to select for 2,4‐D tolerance in red clover with a recurrent selection strategy.…”
mentioning
confidence: 99%
“…Most legumes, including birdsfoot trefoil, are susceptible to 2,4-D, but birdsfoot trefoil is more tolerant than many other legumes. Recognition of this fact led to development of a 2,4-D-tolerant selection of trefoil, T-68, from the Viking variety using the technique of recurrent selection (5). Mor phologically, T-68 is similar to Viking.…”
Section: Introductionmentioning
confidence: 99%
“…Blacklow and Linscott (1) reported that absorption was essentially the same in both varieties, but slightly more 2,4-D is bound in nonalcohol-soluble components in T-68 than in Viking. Devine et al (5) noted that T-68 has twice the surface wax and cuticle of Viking, and the waxes differ in quality. Swanson and Tomes (12) compared T-68 with 'Leo', a Canadian trefoil, and found regeneration of T-68 in tissue culture after 2,4-D treat ment slower than Leo regeneration.…”
Section: Introductionmentioning
confidence: 99%